SUMOylation as a regulatory mechanism for the Sox3 transcription factor - Alfassam, Haifa (2019)
Evidence of the essential role played by Sox3 in cell proliferation and cancer survival is increasing, highlighting the importance of understanding the mechanisms that regulate the function of the Sox3 protein. It has been shown that Sox3 plays a crucial role in embryonic and adult neural stem cells by slowing down proliferation to regulate the stem cells state. Sox3 exerts these functions by working as transcriptional activator and repressor of target genes. It is still not clear how these two functions of Sox3 are regulated. In this study, I was interested in understanding how Sox3 can switch between these two functions, investigating whether this change in activity is linked to SUMOylation.